2018
DOI: 10.1177/1077558718793070
|View full text |Cite
|
Sign up to set email alerts
|

Projected Contributions of Nurse Practitioners and Physicians Assistant to Buprenorphine Treatment Services for Opioid Use Disorder in Rural Areas

Abstract: The United States is experiencing an opioid use disorder epidemic. The Comprehensive Addiction and Recovery Act allows nurse practitioners (NPs) and physician assistants (PAs) to obtain a Drug Enforcement Administration waiver to prescribe medication-assisted treatment (MAT) for opioid use disorder. This study projected the potential increase in MAT availability provided by NPs and PAs for rural patients. Using workforce and survey data, and state scope of practice regulations, the number of treatment slots th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…A recent study found that more restrictive scope of practice laws were associated with fewer NPs with buprenorphine waivers; however, no significant effect was found for PAs and scope of practice laws [161]. Less restrictive NP and PA scope of practice laws are particularly important in rural areas where NPs and PAs serve a critical role in healthcare service delivery [162].…”
Section: Availability Of Buprenorphine-waivered Providers In the Usamentioning
confidence: 99%
“…A recent study found that more restrictive scope of practice laws were associated with fewer NPs with buprenorphine waivers; however, no significant effect was found for PAs and scope of practice laws [161]. Less restrictive NP and PA scope of practice laws are particularly important in rural areas where NPs and PAs serve a critical role in healthcare service delivery [162].…”
Section: Availability Of Buprenorphine-waivered Providers In the Usamentioning
confidence: 99%
“…DATA 2000 permitted "qualified physicians" who hoped to prescribe buprenorphine within their offices to obtain a DEA waiver to do so. Initially, DATA 2000 allowed physicians to treat up to 30 patients and after 1 year, apply for a waiver to increase the number of patients they could treat to 100 (Andrilla, Patterson, Moore, et al, 2018). It explicitly prohibited physicians from delegating buprenorphine prescribing to nonphysicians including NPs even if they had a DEA number and lived in a state without barriers to prescriptive authority.…”
Section: What's the Background?mentioning
confidence: 99%
“…Given the state of rural mental health affairs, PMHNPs and physician colleagues are equipped to organize and advocate politically for PMHNP full scope of practice (i.e., independent practice) and challenge constraining mandated physician supervision (Andrilla, Patterson, Moore, Coulthard, & Larson, 2018; Chapman, Toretksy, & Phoenix, 2019; de Nesnera & Allen, 2016; Delaney et al, 2018; Spetz, Skillman, & Andrilla, 2017). Mandated supervision is financially costly, falsely justifies unequal reimbursement for comparable work, supports inequitable professional relations, increases administrative burden, and overall decreases mental health access to services from all involved providers (Chapman et al, 2019; de Nesnera & Allen, 2016).…”
Section: Psychiatric Mental Health Nurse Practitioner Solutions For Rmentioning
confidence: 99%
“…States with full-practice rights for PMHNPs demonstrate increased service provision to vulnerable and rural populations and associated cost savings, improved self-reported mental health among patients, and decreased mental health–related mortality (Alexander & Schnell, 2019; Martsolf, Auerbach, & Arifkhanova, 2015; Phoenix, Hurd, & Chapman, 2016; Xue, Ye, Brewer, & Spetz, 2016). Of note, PMHNPs with independent practice rights working in community mental health clinics provided twice as many mental health visits and treated more patients compared with colleagues in states who did not have independent practice rights and can combat the opioid crisis after obtaining a prescribing waiver (e.g., buprenorphine) once they have completed a 24-hour training (Andrilla et al, 2018; Substance Abuse and Mental Health Services Administration, 2017; Tierney, Finnell, Naegle, LaBelle, & Gordon, 2015; Yang et al, 2017). Overall, the PMHNP workforce is growing—it is essential that state policies reflect practice autonomy, Drug Enforcement Administration prescribing rights, acute care admitting privileges, expanded clinical roles, and independent billing to support PMHNP presence, satisfaction, and position longevity in rural areas (Chapman, Phoenix, Hahn, & Strod, 2018; Delaney, Drew, & Rushton, 2019; Owens, 2019; Spetz et al, 2017).…”
Section: Psychiatric Mental Health Nurse Practitioner Solutions For Rmentioning
confidence: 99%